Methods for use of insecticides in control of the rice water weevil Oryzophagus oryzae (COLEOPTERA CURCULIONEDAE) - Martins, José Francisco da Silva; Bertels, Andrej; Dittrich, Renato César (Pesquisa Agropecuaria Brasileira, 2014)
Two field experiments with rice were conducted at Rio Grande do Sul, Brazil, with the principal finality of studying the efficiency of two methods in control of the rice water weevil, in relation to the injuries these larvas cause in the roots or "root maggots". The results obtained demonstrated that both the treatment of seeds with insecticides in powder that has effect by contact and digest (preventive method), and the application of granulated and solvable systemic insecticides (control method) protected the roots and proportionated an increase in the yield of rice. It was observed a great and more uniform germination, when the treatment of the seeds with insecticides and fungicides was realized.